Carotid Body Tumor - Hussen, Waleed M. Hussen (Journal of the Faculty of Medicine Baghdad, 2009)
Summary Background:-Carotid body tumors is an uncommon disease entity in Iraq , presented with painless swelling below the angle of the mandible , and is usually benign .The author reviews his personal surgical challenge with eight cases having had this tumor during twelve years period Patients and Methods:-Eight patients with carotid body tumors were managed during twelve years period (1994- 2005) in the Thoracic and Vascular Department of the Medical City Teaching Hospital in Baghdad, Iraq Results:-These patients were retrospectively studied as regard their age, gender, clinical features, diagnostic methods, operative findings, surgical techniques and postoperative outcome. Conclusion:-Early presentation and surgical intervention limit the number of inoperable patients thus avoiding local invasion and malignant changes and leading to fruitful surgical results. Key Words: Carotid Body Tumor (CBT) , Common carotid Artery (CCA)